Results From the WAGR Syndrome Patient Registry: Characterization of WAGR Spectrum and Recommendations for Care Management - Duffy, Kelly A.; Trout, Kelly L.; Gunckle, Jennifer M.; Krantz, Shari McCullen; Morris, John; Kalish, Jennifer M. (Frontiers in Pediatrics, 2021)
WAGR syndrome is a rare genetic disorder characterized by Wilms tumor, Aniridia, Genitourinary anomalies, and Range of developmental delays. In addition to the classic features, patients affected by WAGR syndrome can develop obesity and kidney failure, and a wide variety of nonclassical manifestations have also been described. This suggests that a broader phenotypic spectrum beyond the classic syndrome exists and here we demonstrate that spectrum using data from the WAGR Syndrome Patient Registry. In the present study, we collected information from 91 individuals enrolled in the registry to explore self-reported health issues in this patient population. A wide variety of common clinical issues not classically associated with the disorder were found, prompting the redefinition from WAGR syndrome to WAGR spectrum disorder to incorporate the phenotypic variations that occur. A comprehensive care management approach is needed to address the wide range in clinical issues and we propose a care model for patients affected by WAGR spectrum disorder. Further research is needed to solidify the breath of the phenotype and confirm the observations in this study to advance individualized patient care in this population.